TWO-TIER ITEM TEST IS TO EXAMINE THE CONCEPTUAL OF MECHANIC MOTION FOR CLUES ABOUT CRITICAL THINKING SKILLS - Wawan Bunawan (Jurnal Pendidikan Fisika, 2020)
Critical thinking skills is one way to be able to understand the scientific concepts that exist in physics content as a whole in this case represented by motion content. The aim of the research is to find critical thinking skills behind success and failure in understanding the motion concepts of prospective science teachers. The concept of mechanical motion is expressed in verbal, formal, graphical, and numerical representations. The concept of motion is the subject of the problem in the first tier of the test item. The second tier of the test item measures one of the four critical thinking skills that are relevant to the subject matter. The critical thinking skills studied are reasoning effectively, using systems of thinking, making judgments and decisions, and solving problem. The results of the study show coherence between the ability to understand concepts and critical thinking skills expressed by the correlation index. The magnitude of the correlation index shows the level of coherence between understanding the concept and the underlying critical thinking skills. Empirical data shows a high correlation value between verbal representation and reasoning effectively, formal representation with using system thinking, graph representation with making judgments and decision, and numerical representation with the solving problem skills